LANDASAN SEJARAH, SOSIOLOGIS DAN POLITIS KONSEP WAWASAN NUSANTARA DALAM MEMPERSATUKAN KEBERAGAMAN BANGSA INDONESIA - Rayhan, Akmal; Fatihah , Diniatul Syifa; Fauzia , Fasya; Salsabila , Salwa; Taun (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Wawasan Nusantara is the basic concept of the Indonesian state which has a strong historical, sociological and political foundation.Historically, this concept is rooted in the history of the struggle for independence and the formation of a unitary state in the Unitary State of the Republic of Indonesia. Sociologically, Wawasan Nusantara reflects the socio-cultural diversity of Indonesian society which consists of various tribes, religions, races and groups, but is still connected into one whole. Politically, Wawasan Nusantara is the basis of Indonesia's efforts to strengthen national unity and territorial sovereignty as an archipelagic country. The essence of Wawasan Nusantara is to view Indonesia as a territorial, political, socio-cultural, economic, defense and security unit. This concept reflects the integrity and integrity of the Indonesian archipelago which is composed of various elements but remains one unit. The urgency of Archipelago Insight for Indonesia is very high, especially considering the dynamics of life that continue to develop and the challenges that change over time. Wawasan Nusantara is a visionary foundation for efforts to strengthen national integration, regional sovereignty and development in various areas of life.